Sense of Place Pasar 16 Ilir Palembang - Tutur Lussetyowati; Almira Ulfa (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2023)
A sense of place is an important element that can strengthen the relationship between the user and the place. The character of a place greatly influences how a person evaluates and interprets it. The 16 Ilir Market, one of Palembang's oldest markets, has played an important role in the city. But now, the market is starting to face many problems, such as congestion problems and the physical shape of the building. In addition, the interior of the building becomes less attractive. These factors influence the sense of place at 16 Ilir Market. The purpose of this research is to look at the current sense of place at Pasar 16 Ilir, which is influenced by several aspects. The analysis will refer to several aspects that can give rise to a sense of place for users, such as: activity; meaning; and physical setting. The method used is a qualitative research method, which consists of collecting field data and interviewing managers, merchants, and visitors. Then the data was processed using the descriptive analysis method. According to the study's findings, the sense of place in 16 Ilir Market is shaped not only by the market itself, but also by the surrounding area. Interestingly, the area around the market has a bigger role in creating the sense of place.